Design And Developmentof Actuation Part Of Piezoelectric Generator Prototyping For Alternative Power Generation - R. A., Bakar (2010)
Piezoelectric materials were known as smart materials due to the ability to produce electric potential in response to applied mechanical actions. The materials are expected to become another advantage for automotive industry and also in alternative power generation field. New opportunities for innovative design and development of becoming generation low-cost and high performance piezoelectric application on the latest technologies will be illustrated in the following segments. The complete steps for designing and developing an innovative piezoelectric generator prototype by using 4-axis machine including the factors considered for the best design will be presented. The process consist of designing the model refer to generator working principal and some new fabrication methods for the small thickness plate to be used for the piezoelectric generator.